Q. 745.0( 1 Vote )

# Verify mean value theorem for each of the functions given

f(x) = x^{3} – 2x^{2} – x + 3 in [0, 1]

Answer :

Given: f(x) = x^{3} – 2x^{2} – x + 3 in [0,1]

Now, we have to show that f(x) verify the Mean Value Theorem

First of all, __Conditions of Mean Value theorem__ are:

a) f(x) is continuous at (a,b)

b) f(x) is derivable at (a,b)

If both the conditions are satisfied, then there exist some ‘c’ in (a,b) such that

Condition 1:

f(x) = x^{3} – 2x^{2} – x + 3

Since, f(x) is a polynomial and we know that, every polynomial function is continuous for all x ∈ R

⇒ f(x) = x^{3} – 2x^{2} – x + 3 is continuous at x ∈ [0,1]

Hence, condition 1 is satisfied.

Condition 2:

f(x) = x^{3} – 2x^{2} – x + 3

Since, f(x) is a polynomial and every polynomial function is differentiable for all x ∈ R

f’(x) = 3x^{2} – 4x – 1

⇒ f(x) is differentiable at [0,1]

Hence, condition 2 is satisfied.

Thus, Mean Value Theorem is applicable to the given function

Now,

f(x) = x^{3} – 2x^{2} – x + 3 x ∈ [0,1]

f(a) = f(0) = 3

f(b) = f(1) = (1)^{3} – 2(1)^{2} – 1 + 3

= 1 – 2 – 1 + 3

= 4 – 3

= 1

Now, let us show that there exist c ∈ (0,1) such that

f(x) = x^{3} – 2x^{2} – x + 3

On differentiating above with respect to x, we get

f’(x) = 3x^{2} – 4x – 1

Put x = c in above equation, we get

f’(c) = 3c^{2} – 4c – 1 …(i)

By Mean Value Theorem,

⇒ f’(c) = -2

⇒ 3c^{2} – 4c – 1 = -2 [from (i)]

⇒ 3c^{2} – 4c -1 + 2 = 0

⇒ 3c^{2} – 4c + 1 = 0

On factorising, we get

⇒ 3c^{2} – 3c – c + 1 = 0

⇒ 3c(c – 1) – 1(c – 1) = 0

⇒ (3c – 1) (c – 1) = 0

⇒ (3c – 1) = 0 or (c – 1) = 0

So, value of

Thus, Mean Value Theorem is verified.

Rate this question :

Verify the Rolle’s theorem for each of the functions

f(x) = x (x – 1)^{2} in [0, 1].

The value of c in Rolle’s theorem for the function f(x) = x^{3} – 3x in the interval

For the function the value of c for mean value theorem is

Mathematics - ExemplarVerify the Rolle’s theorem for each of the functions

Mathematics - Exemplar

Verify the Rolle’s theorem for each of the functions

f(x) = log (x^{2} + 2) – log3 in [– 1, 1].

Verify the Rolle’s theorem for each of the functions

f(x) = x(x + 3)e^{-x/2} in [–3, 0].

Discuss the applicability of Rolle’s theorem for the following functions on the indicated intervals :

f(x) = 3 + (x – 2)^{2/3} on [1, 3]

Using Rolle’s theorem, find the point on the curve y = x(x – 4), where the tangent is parallel to x-axis.

Mathematics - ExemplarVerify the Rolle’s theorem for each of the functions

Mathematics - Exemplar